Escape Room: Desktop 3d Game Application For Grammar Lesson Using First Person View Game Genre - Lim, Najmi; Senan, Norhalina (Applied Information Technology And Computer Science, 2025)
Traditional grammar teaching methods, such as lectures and repetitive drills, often less effective to engage high school students. With advanced technology, there are various types of existing interactive apps on english grammar were created such as existing apps like Duolingo and LearnEnglish Grammar. However, its only focus on repetitive tasks with limited interactivity and feedback, further decreasing interest. Escape Room: Desktop 3D Games Application for Grammar Lesson integrates grammar learning with a first person view game designed for students aged 16 to 17 and above.Developed using the Game Development Life Cycle (GDLC) methodology, the game features modules like grammar correction challenges and sentence matching tasks, offering feedback and hints. Using storytelling and interactive puzzles, the game promotes critical thinking and problem-solving skills. After comprehensive testing, the game achieved an average System Usability Scale (SUS) score of 81%, which falls under the category of an acceptable level of user satisfaction, with a grade of B and an adjective rating of Excellent. User feedback has been gathered and highlighting the game’s advantages, such as its immersive learning experience and educational impact. Overall, Escape Room: Desktop 3D Game Application for Grammar Learning demonstrates its potential to be an engaging game with strong educational and entertainment value.